6+(-5w)=26

Simple and best practice solution for 6+(-5w)=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+(-5w)=26 equation:


Simplifying
6 + (-5w) = 26

Solving
6 + (-5w) = 26

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + (-5w) = 26 + -6

Combine like terms: 6 + -6 = 0
0 + (-5w) = 26 + -6
(-5w) = 26 + -6

Combine like terms: 26 + -6 = 20
(-5w) = 20

Divide each side by '-5'.
w = -4

Simplifying
w = -4

See similar equations:

| 2x/2.2x106-4=9.78 | | -3x+4i=2yi+9 | | 8x-5+7x+1=180 | | 5/9[F-32]=25 | | (300+X-600)*1500=(420+y-1500)*600 | | -56-2=-9-49 | | 7/10x88 | | 8(4K-4)=-5+-32 | | 2r^2+r-10=0 | | 3/6=11/x | | log(x+90)=3-logx | | 7(4x+2y)= | | 12+2x+6=360 | | -17-s+6=15 | | V=0.3lwh | | -51/2+22/5p=71/9 | | -13-s+6=15 | | 13-s+6=15 | | 17-x=1/3x(21) | | 46.80=9g+3.69 | | x=0.4y+168 | | 17-s+6=15 | | 7x+14-7x=-4-10 | | 1.76g+-7=0.92 | | 2x+112+6=360 | | 1.76-7=0.92 | | X-17.3=4.7 | | 10=R | | 6x^2+36x+41=0 | | 2x+112+6=180 | | -5(1-3n)-10=-30 | | 8x-16+2x=64+3x |

Equations solver categories